School architectural standards and the expansion of Elementary School in the beginning of the twentieth century in Brazil - Fernandes, Fabrícia Dias da Cunha de Moraes; Alaniz, Erika Porceli (Revista Eletrônica de Educação, 2016)
Abstract This paper aims to describe the transformation that took place in the physical space of elementary schools in Brazil, within the initial period of expanding access to basic education, which occurred between the years 1930 to 1940. Through the historical - descriptive approach, it was sought to demonstrate that the school’s architectural projects have materialized constituent aspects of current educational policies in the indicated periods. Based on a bibliographic research of historical framework, it was approached the emergence of new planning guidelines in state bodies and, the configuration of the Brazilian school architecture in accordance with the modernizing discourse of the period. Were sought the transformations of architectural models and the orientation change of planning bodies, which have used functionalist concepts from the architecture of modern movement for the construction of school buildings, following modular construction principles, prefabrication and despoliation of all ornamentation. Having as reference the modifications in planning guidelines and, how the school physical network has been configured, it was identified that the expansion of the physical network followed the parameter of public spending rationalization. This factor corroborated with the massive access, occasioning the adoption of standardized architectural solutions, impoverishment and precariousness of physical structure of Brazilian public schools. Keywords: School Architecture. Educational Policy. Expansion of physical school network. Padrões arquitetônicos escolares e expansão do Ensino Fundamental no início do século XX no Brasil Resumo O artigo propõe descrever a transformação ocorrida no espaço físico das escolas de ensino fundamental no Brasil, no período inicial da expansão do acesso à educação básica, ocorrida entre os anos 1930 a 1940. Procurou-se, por meio da abordagem histórico-descritiva, demonstrar que os projetos arquitetônicos escolares materializaram aspectos constitutivos das políticas educacionais vigentes nos períodos indicados. Abordou-se, com base na pesquisa bibliográfica de aporte histórico, a emergência de novas diretrizes de planejamento nos órgãos estatais e a configuração da arquitetura escolar brasileira em conformidade com o discurso modernizador do período. Perseguiu-se as transformações dos modelos arquitetônicos e a mudança de orientação dos órgãos de planejamento, os quais utilizaram-se de conceitos funcionalistas da arquitetura do movimento moderno para a construção dos prédios escolares, seguindo princípios construtivos modulares, pré-fabricação e despojamento de toda ornamentação. Tendo como referência as modificações nas diretrizes de planejamento e a forma como configurou-se a rede física escolar, identificou-se que a expansão da rede física seguiu o parâmetro de racionalização do gasto público. Esse fator corroborou para a massificação do acesso, ocasionou a adoção de soluções arquitetônicas padronizadas, o empobrecimento e a precarização da estrutura física das escolas públicas brasileiras. Palavras-chave: Arquitetura escolar. Política educacional. Expansão da rede física escolar.